Multiple positive solutions for singular anisotropic Dirichlet problems - Liu Zhenhai; Papageorgiou Nikolaos S. (2021)
We consider a nonlinear Dirichlet problem driven by the variable exponent (anisotropic) p-Laplacian and a reaction that has the competing effects of a singular term and of a superlinear perturbation. There is no parameter in the equation (nonparametric problem). Using variational tools together with truncation and comparison techniques, we show that the problem has at least two positive smooth solutions.